2019
DOI: 10.5761/atcs.cr.17-00223
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical Fixation Using Bio-Absorbable Plates for Frail Chest in a Severe Osteoporotic Octogenarian

Abstract: We present a case of a severe osteoporotic octogenarian who sustained serious flail chest from a traffic accident. The 3rd–9th ribs of the right chest wall were fractured. Non- operative management was unsuccessful. We performed a surgical fixation using a bio- absorbable and bio-active mini-plating set. This plating set is unsintered hydroxyapatite (u-HA) particles/poly-L-lactide (PLLA) composite osteosynthesis device commonly used for cranial, oral, and maxillofacial surgeries. The use of the u-HA/PLLA devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Regarding osteoconduction, numerous studies using rabbit models have demonstrated the osteoconductive ability and bone bonding features of u-HA/PLLA [7,8,9]. Thus, u-HA/PLLA is used extensively as bone plates and screws for osteosynthesis in different surgical specialties such as orthopedics, plastic surgery, or thoracic surgery [10,11,12,13]. However, these animal experiments only tested the osteoconductive ability of u-HA/PLLA using a rod inserted fully into the knee, such that there was full bone contact.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding osteoconduction, numerous studies using rabbit models have demonstrated the osteoconductive ability and bone bonding features of u-HA/PLLA [7,8,9]. Thus, u-HA/PLLA is used extensively as bone plates and screws for osteosynthesis in different surgical specialties such as orthopedics, plastic surgery, or thoracic surgery [10,11,12,13]. However, these animal experiments only tested the osteoconductive ability of u-HA/PLLA using a rod inserted fully into the knee, such that there was full bone contact.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The use of absorbable plates has also been described in the literature, although much less frequently. [11][12][13][14][20][21][22][23][24][25] One potential advantage of absorbable plates is that they will be resorbed over time gradually transferring the stress load to bone preventing stress shielding which is a reduction in bone density as a result of stress removal from the bone by an implant. 11,14 This transfer of the stress load may stimulate faster bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these systems use metal for permanent fixation with excellent outcomes 4,5 . The use of absorbable plates has also been described in the literature, although much less frequently 11–14,20–25 . One potential advantage of absorbable plates is that they will be resorbed over time gradually transferring the stress load to bone preventing stress shielding which is a reduction in bone density as a result of stress removal from the bone by an implant 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…After 13 years, Oyamatsu et al (26) proposed a U-shaped bioresorbable plate (SuperFIXSORB MX40) with ethibond 0/0 nonabsorbable fixing points for the treatment of flail chest. Recently, Waseda et al (27) described the same procedure in a severe osteoporotic octogenarian with serious flail chest due to a traffic accident, using resorbable Vicryl threads for fixation. The device would be partially reabsorbed at the 4-year follow-up and theoretically completely reabsorbed with another 2 years.…”
Section: Bioresorbable Materialsmentioning
confidence: 99%